Bertrand Meyer: Software Engineering and the Eiffel Programming Language. - Severance, Charles (Computer (00189162), 2012)
For more than 30 years, Bertrand Meyer has taught the computer science field about formal software engineering and object-oriented approaches; he continues do so through his many books, conferences, and Eiffel. The Web extra at http://youtu.be/tEJZF73IfNs is a video interview with Bertrand and Annie Meyer about the Eiffel programming language, software engineering, and object-oriented approaches. The Web extra at http://youtu.be/MDay25r8BZ8 is an audio recording of author Charles Severance's Computing Conversations column, in which he discusses his interview with Bertrand and Annie Meyer about the Eiffel programming language, software engineering, and object-oriented approaches.